2008
DOI: 10.1016/j.taap.2008.05.024
|View full text |Cite
|
Sign up to set email alerts
|

LY294002 inhibits glucocorticoid-induced COX-2 gene expression in cardiomyocytes through a phosphatidylinositol 3 kinase-independent mechanism

Abstract: Glucocorticoids induce COX-2 expression in rat cardiomyocytes. While investigating whether phosphatidylinositol 3 kinase (PI3K) plays a role in corticosterone (CT) induced COX-2, we found that LY294002 (LY29) but not wortmannin (WM) attenuates CT from inducing COX-2 gene expression. Expression of a dominant-negative mutant of p85 subunit of PI3K failed to inhibit CT from inducing COX-2 expression. CT did not activate PI3K/AKT signaling pathway whereas LY29 and WM decreased the activity of PI3K. LY303511 (LY30)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…PI3K/Akt is a well-established upstream kinase phosphorylating GSK-3 at Ser residues, leading to inhibition of GSK-3 activity. Previous studies from our laboratory have demonstrated that CT does not activate PI3K/AKT pathway [21]. Here we found that CT treatment did not affect intracellular distribution of GSK-3 or GSK-3 phosphorylation, either at Ser or Tyr residues.…”
Section: Discussionsupporting
confidence: 49%
“…PI3K/Akt is a well-established upstream kinase phosphorylating GSK-3 at Ser residues, leading to inhibition of GSK-3 activity. Previous studies from our laboratory have demonstrated that CT does not activate PI3K/AKT pathway [21]. Here we found that CT treatment did not affect intracellular distribution of GSK-3 or GSK-3 phosphorylation, either at Ser or Tyr residues.…”
Section: Discussionsupporting
confidence: 49%
“…On the other hand, the mRNA level of DNA-PK is much higher in 4-AP group and shows a slight change in TEA group. Previous research reported that DNA-PK failed to prevent expression of cyclooxygenase-2 expression; however, TEA attenuates expression of cyclooxygenase-2 (33). It provides evidence that TEA and DNA-PK mediate different pathways in COX-2 expression, and the same is true in the apoptotic process.…”
Section: Tea Inhibits Hela Cell Proliferation and Induces Cellmentioning
confidence: 71%
“…A previous finding has demonstrated that PI3K plays a key role in corticosterone-induced COX-2 expression (52). Several studies have shown that EGFR kinase-mediated activation of the PI3K/Akt pathway is required for Zn 2ϩ -induced COX-2 expression (55).…”
Section: Involvement Of Egfr and Pdgfr In Cse-induced Cox-2 Expressiomentioning
confidence: 98%